Music therapy as a therapeutic tool and its interfaces with pediatric nursing (International Seven Journal of Multidisciplinary, 2023)
Introduction: Music in its historical context is part of human life. Its comprehension, perception and understanding goes beyond technological advancement, even considering the technical and scientific evolution of humanity, the mysteries related to musicality are indecipherable, given that it is an exclusive perception of the human species. It’s present in all cultural axes, hence in the hospital environment it is a very powerful therapeutic tool. In addition, the practice in nursing intervention can be considered a powerful instrument in the humanization of care. It’s capable of relaxing, cheering and motivating individuals, because a child is hardly indifferent to music. A musical arrangement has great power as a connection link between people, in this case, reaching the deepest chords of the soul, building a relationship of empathy between them. In this way, harmony and sound vibrations resonate and provide transformation, balance, and healing, resulting in smiles, affection, therapeutic touch, as well as the transmission of security, peace and encouragement. As art, music has a great emotional impact, because it involves people in the energy that the artist put into the work. Eventually, it motivates the patient to feel other emotions by musical interaction, reverberating in many spheres of the hospital and that’s why music expands communication and people's sensitivity, in a coherent way with the place, respecting the specificities of the hospital, musical harmony can add positively to pediatric nursing care. Objective: analyzing the effects of music therapy on the practice of nursing care for pediatric patients, focusing on humanizing care. Method: the study undergoes a qualitative methodological approach, with an explanatory descriptive character, through the integrative literature review (INR) on national and international publications in representative journals in the nursing area, indexed to the virtual database within the period defined for this research, from 2016 to 2021. Results: 50 articles were obtained, among which 5 were included in this review as they met the research goal. Divided into five categories: humanization and music therapy, music therapy as a therapeutic tool; music therapy in the pediatric inpatient unit; music therapy in the neonatal inpatient unit; and music therapy in the pediatric oncology unit. Final considerations: music therapy, as a humanization tool, provides great benefits to hospitalized children who often go through periods of anxiety, anguish, stress, fear and suffering. Children assisted under the intervention of music have the possibility to reflect on existential meanings that help them to strengthen themselves, achieving internal changes that coping with the disease provides. The use of this tool by the nursing team is still a challenge, requiring greater awareness, because although some advances in the area have taken place, it is still contested by health professionals who are unaware of their therapeutic actions and methods. Therefore, hospital must be a space for human development, aimed at welcoming and promoting individualized and humanized health.